Integration of Wafa Method with Quantum Teaching Learning Model: The Smart Way to Educate Learners to Memorize the Quran - Rohmah, Alif Istiadatir; Nawangsari, Dyah; Supriadi, Supriadi (International Journal of Multidisciplinary Research of Higher Education, 2025)
The right method is needed to facilitate the process of memorizing the Quran effectively and enjoyably. Without an appropriate method, the achievement of memorization can be hampered both in quality and consistency. This study aims to explore how the implementation of the wafa method and the Quantum Teaching approach in memorizing the Quran. This research method uses descriptive qualitative research method through case study approach. The research informants totaled nine informants consisting of the principal, vice principal of the curriculum section, coordinator of the wafa method, Quran teacher, and five student representatives from each level. Data collection techniques were carried out through observation, interviews and documentation. Data analysis techniques use Milles, Huberman and Saldana theoretical techniques which include data collection, data reduction, data presentation and conclusion drawing. Data validity techniques were carried out through source triangulation and technique triangulation techniques. The results of the research implementation show that i). Program planning begins with preparing Teaching Modules, Syllabus, Semester Program, Annual Program and Wafa Method Companion Book, ii). Program implementation includes opening, experience, material planting, assessment and closing (5P) through the application of the Tanamkan, Alami, Namai, Demonstrasikan, Ulangkan and Rayakan (TANDUR) strategy as an effort to increase students' learning participation through kinesthetic methods, iii). Learning evaluation. The implications of this study indicate that the application of the Wafa method and the Quantum Teaching approach is able to create a more structured, fun, and participatory learning process for memorizing the Quran. The benefits are seen in the increase in motivation, emotional involvement, and memory of students, which overall contributes to the achievement of Islamic religious education goals more optimally.